Ecological Functions of Vertebrate Scavenging - Beasley, James C.; Olson, Zachary H.; Selva, Nuria; DeVault, Travis L. (DigitalCommons@University of Nebraska - Lincoln, 2019)
Introduction The role of vertebrate scavenging in food web dynamics has historically been minimalized and portrayed as the activity of a select group of obligate scavengers (e.g., vultures), with a simplistic linkage between carrion and detritivores in food webs. Research in the last few decades, however, has revealed that the role of carrion in food web dynamics is severely underestimated, highly complex, and pervasive among ecosystems across the globe (DeVault et al. 2003; Selva and Fortuna 2007; Wilson and Wolkovich 2011). Such observations have led to a surge in research interest in scavenging ecology that continues to reveal new information on the ecological functions of scavenging and the complex role scavengers play in the cycling of nutrients within ecosystems. Although the functional role of scavengers in ecosystems has been recognized by some ecologists for many years, the importance a single guild of scavengers can have on ecosystem processes was underappreciated by many prior to the collapse of Gyps vulture populations in Asia in the 1990s due to accidental poisoning with diclofenac, a non-steroidal anti-inflammatory drug that was administered to cattle (Oaks et al. 2004). This tragedy has served as a cornerstone example of the ecosystem services provided by scavengers, as well as the potential impacts of anthropogenic activities on ecosystem function (DeVault et al. 2016). Scavengers have historically been some of the most persecuted species across the globe (Ogada et al. 2012a). However, while direct persecution remains a threat to scavengers in some areas, ecosystem services provided by scavengers also are being eroded due to numerous other anthropogenic factors (e.g., climate change, trophic downgrading, habitat loss and fragmentation, contaminants). Many of these factors have far reaching impacts, from the deep sea to arctic ecosystems, and have the potential to disrupt nutrient cycling dynamics across all levels of biological organization. As a rapidly growing sub-discipline within the field of ...